Determinants of Intention to Use the TikTok Application among Generation Z - Fitria Halim; Fedianty Augustinah; Deandra Vidyanata; Sherly Sherly; Acai Sudirman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The urgency of the study is to analyze the effect of perceived ease of use, perceived enjoyment, and facilitating conditions on the intention to use the TikTok application service in the generation Z group in Indonesia. This research instrument uses an online questionnaire distributed to 210 respondents who are none other than users of the TikTok application from the generation Z group. Next, the researchers tested the hypothesis using a variant-based Structural Equation Modeling (SEM) called Partial Least Square (PLS) and the SmartPLS version of the application. 3.0 as a tool to analyze it. The results of this research conclude that perceived ease of use, perceived enjoyment and facilitating conditions have a positive and significant effect on intention to use. The results of this research prove that factors such as perceived ease of use, perceived enjoyment, and facilitating conditions are important components in the formation of intention to use, so for TikTok application developers this can be taken into consideration for the improvement of TikTok application services in the future. Urgensi penelitian untuk menganalisis pengaruh perceived ease of use, perceived enjoyment, dan facilitating conditions terhadap intention to use layanan aplikasi TikTok pada kelompok generasi Z di Indonesia. Instrumen penelitian ini menggunakan kuesioner online yang dibagikan kepada 210 respoden yang tidak lain adalah pengguna aplikasi TikTok yang berasal dari kelompok generasi Z. Selanjutnya peneliti menguji hipotesis menggunakan Structural Equation Modeling (SEM) berbasis varian yang disebut Partial Least Square (PLS) dan aplikasi SmartPLS versi 3.0 sebagai alat untuk menganalisisnya. Hasil dari riset ini menyimpulkan faktor perceived ease of use, perceived enjoyment dan facilitating conditions berpengaruh positif dan signifikan terhadap intention to use. Hasil riset ini membuktikan bahwa faktor seperti perceived ease of use, perceived enjoyment, dan facilitating conditions merupakan komponen penting dalam pembentukkan intention to use, sehingga bagi pengembang aplikasi TikTok hal ini dapat dijadikan sebagai bahan pertimbangan guna penyempurnaaan layanan aplikasi TikTok di masa yang akan datang.